Faktor-Faktor Yang Mempengaruhi Kepuasan dan Loyalitas Nasabah Elektronik Pengguna M-banking Bank Syariah Indonesia - Farida, Siti Nur; Siti Zulaikha (Universitas Islam Negeri Alauddin Makassar, 2024)
Mobile banking is a mobile technology innovation provided by retail banks and microfinance institutions in developed and developing countries, the existence of m-banking has the potential to have a major impact on market share. Customer satisfaction and loyalty are important factors in the development and management of Islamic banking. This study aims to determine the effect of electronic service quality factors through six dimensions on customer satisfaction and loyalty. Some factors that can affect customer satisfaction of m-banking users include the dimensions of comfort, security, convenience, design, application system and personal need. This research uses a quantitative approach with the adoption of SEM-PLS techniques. Primary data of 204 obtained through distributing questionnaires were analyzed using SmartPLS version 4 software, showing the results that the dimensions of convenience, application systems and personal need have a positive and significant effect on satisfaction, satisfaction is proven to have a positive and significant effect on loyalty, while convenience, security and design have no significant effect on customer satisfaction of BSI m-banking users. Research contributes to providing strategic recommendations for marketers and policy makers to increase customer satisfaction and loyalty of Bank Syariah Indonesia customers.